PROGAM BANTU PEMESANAN JASA PERBAIKAN AC STUDI KASUS: CV. KURNIATAMA - Halim Budi Santoso; Darma Cahyadi; Erick Kurniawan (Universitas Bumigora, 2017)
Technology can help Service Provider Company in its business process. This needs due to its difficulties to record its order transactions.Online reservation is hoped to help in recording customer service order. Long and difficult service order transaction will cause pending customer service order. Furthermore, it will decrease the number of served customers. This problem leads the help of online booking system. CV Kurniatama as a Air Conditioner service provider, needs this system to help customer book and reserved online. This system also will record the transactions. This system can be accessed everywhere and everytime. This system will give some limitations to techician in order to serve the customers. By implementing web based system, it can shorten the order process time. This system will bring excellence customer service. By implementing this system, CV Kurniatama will increase its services to customer. Besides, customers also has high flexibility to order. Online reservation will help customer to make customer more comfortable and bring service excellence to the customer. This system also will bring some changes in CV Kurniatama business process.